Assessment of nitrogen utilization from urea applied in rubber seedling nursery using 15N tracer technique - Prasannakumari, P; Jessy, M D; George, Sherin; Meti, Sankar (Journal of Plantation Crops, 2019)
Nitrogen uptake from urea applied to rubber seedlings in the nursery was evaluated using 15N tracer methodology, in micro-plots established in the field. Effect of varying rates of N on growth, and the relative contribution of soil N and fertilizer N towards total N uptake were studied. Influence of rate of N application on growth of seedlings was observed up to three months, and after six months, growth of plants was comparable for all the four N levels. The efficiency of N absorption by the plant, expressed as percentage N utilization ranged from 13.62 per cent at 125 kg N ha-1 to 5.84 per cent at 500 kg N ha-1. The 15N balance sheet averaged over the four levels of N shows that about 9.27 per cent of applied N was taken up by rubber seedlings, about 8.78 per cent remained in 0-60 cm depth of soil and about 81.95 per cent was unaccounted N.